Inclusión de tres niveles de una combinación entre tributirina, levadura hidrolizada y proteinato de zinc para medir el impacto en las variables productivas de Pollos Broiler - Panizo Asimbaya, Sebastian Andrés (2021)
n the present investigation, the inclusion of three levels of a combination of tributyrin, hydrolyzed yeast and zinc proteinate was evaluated to measure the impact on the productive variables of broiler chickens; 70 birds in total, 35 chicks and 35 1-day-old pullets of the Cobb 500 line with an average weight of 0.048 kg were used, which were divided into 4 treatments without repetitions, thus having 17 and 18 chicks respectively in each quadrant.The treatments were identified as T0 control treatment with 17 chicks, T1 treatment with low dose of the combination with 17 chicks, T2 treatment with the medium dose of the combination with 18 pullets, T3 treatment with the highest dose of the combination with 18 pullets.During the reception, water with electrolytes was supplied to hydrate the birds after vaccination, together with the combination included in the commercial feed for each of the treatments, distributed as follows: initial 1 (1 to 7 days of age), initial 2 (8 days to 18 days of age), growth (19 to 28 days of age) and the last stage of fattening (29 to 42 days of age), in each of the stages the combination was included in relation to the amount of feed.